Inclusive Positivism and the Courts: Reconciling Legality and Legitimacy in Contemporary Democracies - Widaningsih (Indonesian Scientific Publication, 2025)
This article critically reassesses legal positivism in the context of contemporary constitutional adjudication. Legal positivism traditionally maintains a strict separation between legal validity and moral reasoning, but modern courts increasingly rely on moral and constitutional principles to justify legal outcomes. This study analyzes four landmark legal texts: Miller v Secretary of State for Exiting the EU (UK), S v Makwanyane (South Africa), Neubauer v Germany, and the European Union’s AI Act. Through doctrinal and comparative methodology, the research explores how judicial reasoning in each case explicitly reflects or diverges from exclusive and inclusive positivist theory. While Miller and the AI Act affirm source-based legality, Makwanyane and Neubauer reveal the judiciary's turn toward principle-based legitimacy. The findings suggest that inclusive positivism, and in some cases interpretivism, better reflects how courts navigate complex rights issues. The article concludes by proposing a hybrid jurisprudential model that retains the structural benefits of legal positivism while incorporating codified moral principles, offering a balanced approach suited to modern constitutional democracies.